¿LA ANEMIA GESTACIONAL IMPACTA EN EL PESO DE LOS RECIÉN NACIDOS? - Segura Paredes, Irving Mijael (2024)
Gestational anemia is a frequent public health problem, especially in pregnant women from developing countries. During pregnancy, iron requirements increase due to fetal growth, placental development, and expansion of maternal blood volume. Low hemoglobin levels may reduce fetal oxygen availability and increase the risk of intrauterine growth restriction, low birth weight, fetal distress, and maternal complications. The article highlights evidence from international studies showing an association between gestational anemia and adverse neonatal outcomes, particularly low birth weight. However, it also notes that more prospective studies are needed in Peru to better evaluate the duration, severity, and early treatment of anemia during pregnancy. Strengthening prenatal care, health education, and iron and folic acid supplementation is essential to improve maternal and neonatal health outcomes.